Legal foundations for public participation on international watercourses: the case of the Ili River - Janusz-Pawletta, Barbara; Oravcová, M. (Informa UK Limited, 2025)
Effective engagement of local communities in managing transboundary water basins is essential to sustainable development and water resources management. This paper explores how international law, including a variety of legal regimes from international water law to international environmental and human rights law, shapes public participation on transboundary water resources. A coherent legal framework secures substantive rights to water and supports its implementation via procedural rights: access to information, justice, and participation in decision-making. Using the Ili River shared by China and Kazakhstan as a case study, this article highlights the legal foundations that enable participation, identifies gaps, and suggests that solutions may lie beyond international water law.